Analisis Perbedaan Indeks Vegetasi Normalized Difference Vegetation Index (NDVI) dan Normalized Burn Ratio (NBR) Kabupaten Pelalawan Menggunakan Citra Satelit Landsat 8 - Valentino Kevin Sitanayah Que; Sri Yulianto Joko Prasetyo; Charitas Fibriani (Indonesian Journal of Computing and Modeling, 2019)
Indonesia became one of the various countries that experienced a forest fire disaster and became the second highest country to lose forests after Brazil was ranked first according to FRA. The purpose of this study is to see changes and differences in the value of vegetation index on forest / burned land in Pelalawan District, Riau Province. The method used in this study is remote sensing analysis, namely the vegetation index Normalized Difference Vegetation Index (NDVI) and Normalized Burn Ratio (NBR). Fire statistics are obtained from riau.bps.go.id and the research data uses Landsat 8 OLI Satellite Imagery.The results of the study found that the NDVI vegetation index value was higher than the NBR vegetation index value, which meant that the NDVI vegetation index in Pelalawan District was classified as good but many areas were burnt and caused considerable losses. NDVI and NBR vegetation index values ​​at 3 time periods experienced a not significant increase and decrease. Pelalawan Regency is at the NBR vegetation index value of 0.123 - 0.529 and the vegetation index value of NDVI at 3 time periods is said to be large with the highest values ​​of 0.448 - 0.543 (> 0.4 good vegetation) which are classified as warm area forests and tropical rain forests. The area of ​​the burning area is at the highest moderate level (moderate-high), which is on 17 November 2016 covering an area of ​​522.708 hectares or almost half of the area of ​​Pelalawan District.